Mathematics literacy task on number pattern using Bengkulu context for junior high school students - Susanta, Agus; Sumardi, Hari; Susanto, Edi; Retnawati, Heri (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
Mathematical literacy has an important role in solving students' real-life problems in supporting literacy skills, teachers can use real contexts as outlined in tasks in-class learning. The Bengkulu context can be used because it is closely related to the environment and students' daily live. This study aims to produce math literacy tasks in the Bengkulu context which are valid and potential impact on student literacy. The research employed a development design with a formative evaluative model using stages of self-evaluation, expert reviews, one-to-one, small group, and field tests. The subjects of the research were students in the eighth grade of a Junior High School in Bengkulu City. Data were collected through questionnaires, documentation, tests, and interviews. This study produced four mathematical literacy tasks with the Bengkulu context that met the criteria of being valid and having a potential impact. Mathematical tasks that are designed with the context can improve students' mathematical literacy activities. The use of tasks with context can be a learning resource that strengthens the introduction of students' local culture.